Correlation between Human Leukocyte Antigen Gene Polymorphism and COVID-19: Incidence and Severity - Raslan, Mohamed Ahmed; Shehata, Eslam Mansour; R., Sara A.; Sabri, Nagwa A. (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Certain risk factors for severity of coronavirus disease-2019 (COVID-19) infection have been reported, including age, and the presence of concomitant metabolic conditions such as obesity, diabetes, and hypertension. Literature search was done to highlight on the possible effect of human leukocyte antigen gene polymorphism on management of COVID-19 patients. It was discovered that there may be a link between human leucocyte antigens and an increased risk of COVID-19. Besides, HLA-G and HLA-E can both induce immunological tolerance. Indeed, they could inhibit innate and adaptive immune responses. The key contributor to the pathophysiological processes of SARS-CoV-2 is an exacerbated immune response caused by viral infection in the host. In extreme circumstances, the immune response is overwhelming, resulting in an inflammatory cytokine storm that causes significant tissue damage and numerous organ failures.